Antioxidant activity and cytotoxicity of Cyrtosperma johnstonii extracts on drug sensitive and resistant leukemia and small cell lung carcinoma cells - Siriporn Okonogi (2018)
Context: The number of patients with cancer is increasing. New therapeutic agents to overcome drug-resistant tumors are urgently needed. Cyrtosperma johnstonii N.E. Br. (Araceae) is used for treatment of cancer in Thai traditional medicine. This study aimed to evaluate antioxidant activity and cytotoxicity of C. johnstonii extracts on human cancer cells. Materials and methods: Dried powder of C. johnstonii rhizomes was extracted with several solvents. The 0.1mg/ml extract solution was tested for antioxidant activity by 2,2′-azinobis-3-ethylbenzothiazoline-6-sulfonic acid (ABTS) and ferric reducing antioxidant power (FRAP) assays. Color formation from 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide was used to determine cell viability. Standardization of the extract was performed by high-performance liquid chromatography (HPLC) with photodiode array detector at 254 and 360nm. Cell cycle arrest was evaluated by flow cytometry after 5min, 12h and 24h treated with 20g/ml of the acetone extract. Results: The acetone extract exhibited the highest phenolic content and antioxidant activity (TEAC and EC values = 19.2±0.14 and 19.2±0.31mM/mg, respectively). The IC50 values for leukemia ranged from 11±1 to 29±3g/ml and from 5±2 to 6±0g/ml for small cell lung carcinoma cells. Cell cycle arrest occurred at the G2/M phase followed by apoptosis. HPLC analysis revealed that rutin is the major constituents of the extract. Discussion and conclusion: The acetone extract of C. johnstoni is a promising source of natural antioxidants and anticancer. The extract inhibits cancer cells effectively with less effect on normal cells. © 2013 Informa Healthcare USA, Inc.